Cuba - Huish, R. (Comparative elite sport development. Systems, structures and public policy, 2025)
Cuba's elite sport development system is well known for punching above its weight when it comes to achieving sports excellence. The system is entirely publicly funded and is designed around early childhood recruitment into elite training circles (Pye & Pettavino, 2016). Training of elite athletes takes place at dedicated facilities where all boarding and education are covered by the state. The Cuban government's strong commitment to sport extends from core revolutionary values of athleticism. Within these values also lie commitment to viewing sport as a grounds for solidarity between nations, especially those in the global South for whom sport can be a means of building national pride and challenging colonial hegemonies. Since the 1980s, Cuba routinely produced outstanding athletes in gymnastics, athletics, boxing, baseball, volleyball, and marksmanship. They have also extended sport scholarships to athletes from over 80 countries around the world. Furthermore, Cuba has hosted major international elite sport events that have worked to promote its own international interests for economic and political cooperation with other nations. The structure of Cuba's elite sport development resembles the programme design of other Socialist Eastern bloc states, however, Cuba differs slightly in its commitment to complementing elite development with universal accessibility to sport (Darnell & Huish, 2017; Green & Oakley, 2001). This strong basis of elite sport development, along with broader practices of sport for development on which these elite goals are grounded, has garnered international recognition and remuneration for Cuba.